Repellent and Anti-Feeding Activity of Cinnamomum tamala Essential Oils against Angoumois Grain Moth Sitotroga cerealella (Olivier) - Kumari, Pallavi; Kumar, Arun (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Stored food faces severe damage due to infestation by insects. The essential oils extracted from leaves and bark of Cinnamomum tamala (Indian bay leaf) by hydro distillation method was screened as fumigant for repellent and antifeedant activity against Angoumois grain moth Sitotroga cerealella in laboratory assay. Fumigation with different concentration of essential oils significantly (P < 0.01) showed repellent action with 100% repellency and antifeeding activity. Highest reduction in feeding deterrence index 76.19% and 80.30% observed in leaf and bark oils of C. tamala essential oils against S. cerealella in comparison to control groups. These studies showed strong insecticidal activity of both essential oils and its potential role as a fumigant against S. cerealella. From this study, it is concluded that these essential oils have potential for application in Insect Pest Management programs for stored-grain insect pests.